Differences in supraspinatus occupation ratio between the symptomatic, the contralateral asymptomatic shoulder and control subjects: A cross-sectional study. Issue 6 (12th February 2021) - Navarro-Ledesma, Santiago; Fernandez-Sanchez, Manuel; Luque-Suarez, Alejandro
Abstract : Abstract: The relationship between supraspinatus tendon thickness and the acromiohumeral distance (AHD) at both rest position and shoulder elevation is still to be explored in those with chronic shoulder pain. The aim is to compare supraspinatus occupation ratio (OR) at 0° and 60° of shoulder elevation measured by ultrasound imaging in the symptomatic shoulder, the contralateral asymptomatic shoulder and in healthy subjects. This was across-sectional, observational study. A sample of 56 participants with subacromial pain syndrome in their dominant arm was recruited in 3 different primary care centres. Forty participants without shoulder pain were also recruited. The AHD at 0° and 60° of active shoulder abduction as well as the supraspinatus tendon thickness were measured by ultrasound in these groups. Supraspinatus OR at 60° was significantly greater in symptomatic compared to asymptomatic shoulders ( P  = .04) and healthy shoulders ( P  = .008). The percentage of change in supraspinatus OR from rest position to 60° was also greater in symptomatic shoulders when comparing with asymptomatic ( P  = .01) and healthy shoulders ( P  = .03). No other statistically significant differences for the rest of comparisons were found. Supraspinatus OR may explain shoulder pain in chronic conditions. Further studies at acute and chronic conditions after a physiotherapy treatment are needed to explore its usefulness in clinical practice.